Effects of Pr₆O₁₁ addition and sintering temperature on structural, optical and luminescence properties of Zn₂SiO₄ based glass ceramics - Mohamed, Nurzilla (2017)
In recent years, great interest was focused on glass ceramics for applications in laser, optical amplifier and optical sensor. Up to now, the commercial Zn2SiO4 were fabricated due to its high luminescence and chemical stability. This research highlights the alternative sources of SLS-ZnO glass in order to produce Zn2SiO4 glass ceramics by varying Pr concentration and sintering temperatures. The six series of Pr addition into SLS-ZnO glasses of the type x(Pr6O11).100-x(SLS0.5-ZnO0.5) (where x = 0, 1, 2, 3, 4, at 5 wt. %) were prepared by mixing the raw materials Praseodymium Oxide (Pr6O11), Soda Lime Silica (SLS)and Zinc Oxide (ZnO) as starting materials in the appropriate amount. Then, these mixture materials were melted at 1400 oC for 2 hours in alumina crucibles by electrical furnace. The molten glass was poured into water by quenching technique in order to produce glass frit. The glass fritz was finely ground and sieved to be in powder form with the size of 63 μm. Density of SLS-ZnO glass increases by increasing Pr concentration. The glass system which consists of amorphous phase and more non-bridging oxygen were confirmed by XRD and FTIR analysis. The band gap fluctuated when Pr concentration is lower than 3 wt.% and enhanced at higher Pr concentration (4 and 5 wt.%). However, the luminescence intensity decreased as the Pr concentration increased from 4 to 5 wt.% may due to the concentration quenching effects. Besides that, Pr doped Zn2SiO4 glass ceramics were prepared by sintering SLS-ZnO glass from 600 to 1000 oC. The properties of Pr addition into Zn2SiO4 were evaluated in terms of structural, optical and luminescence properties at different sintering temperatures. The formation of α-Zn2SiO4 in the SLS-ZnO host matrix is proven by XRD, FTIR, FESEM and EDX analysis. The XRD indicates the peaks of α-Zn2SiO4 increases in intensity with increasing sintering temperatures by increasing Pr concentration from 0 to 2 wt.% Pr. Nevertheless, the intensity of α-Zn2SiO4 phase decreases at 3 wt.% Pr but increases at high Pr concentration (4 and 5 wt.% Pr). The FTIR spectra showed the presence of Zn2SiO4 phase in the glass ceramics network occurring at ~467 and ~697 cm-1 which is supported by EDX analysis. FESEM micrographs showed the grain growth increases with increasing sintering temperatures. The average grain growth decreases as Pr concentration increases from 1 to 5 wt.%. The sharpness absorption band of ~444 nm increases as Pr concentration and sintering temperatures increases which is in good agreement with the excitation of blue LED for the fabrication of White Light Emitting Diode (WLED). The band gap increases with increasing sintering temperatures up to 900 oC and decreases with further sintering of 1000 oC due to the crystallinity of Zn2SiO4 phase. The substitution of Pr addition into the host matrix fluctuates the band gap when Pr concentration is lower than 4 wt.% and decreases at 5 wt.% Pr. The increase in crystallinity of Zn2SiO4 is suggested to be due to the enhancement of the luminescence with increasing sintering temperatures. It is interesting to note that the luminescence intensity decreases by increasing Pr concentration up to 3 wt.% to increase at 4 and 5 wt.% Pr due to the incorporation of the Pr3+ ion in the Zn2SiO4. This suggests that Pr doped Zn2SiO4 possess suitable structural, optical and luminescence properties and could be a promising glass ceramic material for optoelectronics devices.